Aeronautical Research in Germany From Lilienthal until Today - Hirschel, Ernst Heinrich 1934-; Prem, Horst 1940-2019; Madelung, Gero 1928-2018 (Springer Berlin Heidelberg, 2004)
From the pioneering glider flights of Otto Lilienthal (1891) to the advanced avionics of today's Airbus, aeronautical research in Germany has been at the forefront of the birth and advancement of aeronautics. On the occasion of the centennial commemoration of the Wright Brother's first powered flight (December 1903), this English–language edition of "Aeronautical Research in Germany" recounts and celebrates the considerable contributions made in Germany to the invention and ongoing development of aircraft. Featuring hundreds of historic photos and non-technical language, this comprehensive and scholarly account will interest historians, engineers, and, also, all serious airplane devotees. Through individual contributions by 35 aeronautical experts, it covers in fascinating detail the milestones of the first 100 years of aeronautical research in Germany, within the broader context of the scientific, political, and industrial milieus.
Keywords: Engineering; Aerospace Technology and Astronautics; Automotive Engineering; Physics, general; Popular Science, general; Engineering, general; Physics; Popular works; Automotive engineering; Aerospace engineering; Astronautics; Geschichte; Forschung; Luftfahrttechnik; Deutschland; Aufsatzsammlung